Peranan Pohon dalam Membentuk Iklim Mikro: Peranan Pohon Dalam Membentuk Iklim Mikro - Erva Yenri; Eni Suhesti; Azwin Said (Universitas Lancang Kuning, 2023)
Climate affects the metabolism and behavior of living things, on the other hand, the state of the microclimate is affected by the presence of living things. Microclimate components include; air temperature, solar radiation intensity, air humidity, and wind speed. The purpose of this study was: to analyze the role of trees in shaping the microclimate in the Lancang Kuning University campus area. This research was conducted using a survey method and observation of microclimatic conditions through direct measurements in the field. The components of the microclimate that were observed and measured were temperature, sunlight intensity, humidity and wind speed. The results showed that all elements of the microclimate that were measured were better (lower air temperature, higher humidity, lower solar radiation intensity and lower wind speed) under the trees compared to the results of measurements in open places. It is recommended to maintain a good microclimate in the Unilak campus environment to maintain existing trees, and carry out enrichment planting in the Unilak campus area.